Thin Film NCM Cathodes as Model Systems to Assess the Influence of Coating Layers on the Electrochemical Performance of Lithium Ion Batteries. Issue 9 (1st March 2021) - Hemmelmann, Hendrik; Dinter, Julius K.; Elm, Matthias T.
Abstract: A facile procedure is demonstrated to prepare lithium nickel cobalt manganese oxide (NCM) thin film cathodes. Via a sol‐gel approach and subsequent spin‐coating, a crystalline and phase‐pure cathode layer is prepared without any further additives or binders. It is shown that the thin film cathodes are ideal model systems to access the effect of coating layers on electrochemical performance in lithium ion batteries. For this purpose, the thin films are coated with an ultrathin alumina layer using atomic layer deposition. The samples are structurally and electrochemically characterized, exhibiting comparable properties as cathodes prepared from powder. After cycling, post‐mortem analysis is conducted to investigate structural changes inflicted by the electrochemical treatment. The characterization reveals that uncoated samples exhibit severe structural changes due to cycling, while coated samples show only minor changes under the same conditions. Post‐mortem surface analysis using X‐ray photoelectron spectroscopy confirms the corrosion of the uncoated cathode and proofs the scavenging effect of alumina. The presented results provide a simple and versatile method to prepare thin film NCM model systems, which enable an accurate analysis of the cathode–electrolyte interface and thus allow to obtain a deeper understanding of the beneficial effect of coatings for next‐generation lithium ion batteries. Abstract : A simple and facile method to produce thin film lithium nickel cobalt manganese oxide cathodes is presented. Pristine and ALD coated thin film cathodes exhibit qualitatively comparable electrochemical behavior to powder‐based cathode materials. The thin films act as model systems, which enable to unravel surface reactions and their products at the cathode–electrolyte interface using surface‐sensitive techniques.